An Examination of Changes in Emotion Co‐regulation Among Mother and Child Dyads During the Strange Situation. Issue 3 (14th May 2015) - Guo, Yuqing; Leu, Szu‐Yun; Barnard, Kathryn E.; Thompson, Elaine A.; Spieker, Susan J.; Lunkenheimer, Erika S.; Leerkes, Esther M.
<x xml:space="preserve">Abstract</x> The present study applied state‐space grid analysis to describe how preschooler–mother dyads co‐regulate emotion in the Strange Situation. Second‐to‐second mother and child affect during pre‐separation play (baseline) and the final reunion (post perturbation) episodes of the Strange Situation were coded for 80 dyads. Change in emotion co‐regulation across the two Strange Situation episodes was examined with linear mixed models for groups with secure and insecure classifications. The groups did not differ at baseline. Change in content‐specific emotion co‐regulation but not content‐free emotion co‐regulation was found to be significantly different within and between groups. Both secure and insecure dyads reduced the time spent in positive interaction but increased the time in negative interaction across two episodes; the change in secure dyads was less pronounced than in the insecure dyads. After the separation, secure dyads had more positive interactions and fewer negative interactions compared with insecure dyads. Results highlight how secure dyads adapted to the stressful change, whereas insecure dyads were more reactive and less resilient to the stress of the study's brief imposed separation. Copyright © 2015 John Wiley & Sons, Ltd.